Jakost v podniku - Mayer, Daniel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce je zaměřena na jakost v podniku KaPO-oděvy s.r.o. Je zde popsána metodika jakosti ve firmě. V analytické části jsem se zaměřil na identifikaci problémů ve firmě a na zhodnocení celé stávající situace. V další části navrhnu vylepšení, nebo odstranění identifikovaných problémů. Výsledkem návrhu bude zlepšení stávající situace a vylepšení procesu jakosti v podniku. Diplomová práce se skládá z části teoretické, z analýzy problémů a z vlastního návrhu řešení.

The thesis is focused on quality in business-clothes KaPO-oděvy s.r.o. It describes the methodology of quality in the company. The analytical part is focused on identifying problems in the company and to evaluate the whole of the current situation. In the next section suggest improvements, or remove identified problems. The result of the proposal will improve the existing situation and improve the quality of the business process. The thesis consists of the theoretical analysis of problems and design their own solutions.
Quality Management
Keywords: Jakost Podnik Proces Řízení jakosti ISO normy Reklamace Management jakosti; Quality Enterprise Process Quality Control ISO Standards Complaint Quality Management